(untitled) - Gibilisco, Stan (New York, 2008)
For more than fifteen years, Mastering Technical Mathematics has been the definitive self-teaching guide for those wishing to boost their career by learning the principles of mathematics as they apply to science and engineering. Featuring the same user-friendly pedagogy, practical examples, and detailed illustrations that have made this resource a favorite of the scientific and technical communities, the new third edition delivers four entirely new chapters and expanded treatment of cutting-edge topics.
Keywords: Mathematics,Toán học